Middlemen: the good, the bad, and the ugly. - Biglaiser, Gary; Li, Fei (RAND Journal of Economics (Wiley-Blackwell))
Abstract: We examine the role of a middleman as an expert in markets. A seller's effort determines the quality of the good. Buyers observe neither the seller's effort nor the good's quality. A middleman, after observing a signal about the good's quality, decides whether to purchase it and then to sell it. We show that the presence of a middleman may either reduce or exacerbate the seller's moral hazard problem. We also consider a model with multiple middlemen. We find that the seller's effort is minimized if either the middleman's signal is perfect or the number of middlemen is large.